Quantifying the bone marrow composition of the healthy adult wrist with dual-energy CT. Issue 139 (June 2021) - Müller, Felix C.; Gosvig, Kasper K.; Mikkel, Østergaard; Bjarne, Roed; Rodell, Anders; Henrik, Børgesen; Krauss, Bernhard; Gade, Jesper S.; Boesen, Mikael
Highlights: Absolute quantification of bone marrow in the wrist is possible with Dual-Energy CT. Material decomposition parameters for VNCa images should be adjusted. Sex, age and calcium values have a clinically negligible effect on VNCa values. Abstract: Purpose: Purpose of this study was to investigate Dual-energy CT (DECT) derived virtual non-calcium (VNCa) values for absolute quantification of the bone marrow composition in the wrist. Materials and Methods: We prospectively included consecutive adult participants and examined their wrists with DECT. Ranges of VNCa and calcium values were measured in the carpal bones, radius and ulna using a semi-automatic method. Bones with bone marrow edema, assessed by two blinded radiologists, were excluded. After determining optimum parameters for the three-material decomposition, the influence of calcium values, age and sex on VNCa values was assessed using multiple linear regression. Results: 41 participants (Median age 53 years, range 20 years – 88 years, 51 % men) were enrolled and 399 bones assessed. At participant level mean VNCa values were -143 HU (SD 14 HU) using the current parameters for three-material decomposition and -104HU (SD 11 HU) with optimized parameters. There was a strong and significant influence of calcium values on VNCa values with the current parameters (p < 0.001, -0.137 HU[VNCa] / HU[Calcium] ). With optimized parameters the calcium values and sex were not statistically significant predictors of VNCa values. Age was a significant, but clinically negligible, predictor (p = 0.03, -0.225 HU / year). Conclusions: After optimizing three-material decomposition parameters, calcium values, age and sex do not substantially influence virtual non-calcium values, and DECT may therefore be used for absolute quantification of the bone marrow composition - alleviating the need for reference bones or groups.